2022
DOI: 10.3390/cancers14112595
|View full text |Cite|
|
Sign up to set email alerts
|

Design of New Potent and Selective Thiophene-Based KV1.3 Inhibitors and Their Potential for Anticancer Activity

Abstract: The voltage-gated potassium channel KV1.3 has been recognized as a tumor marker and represents a promising new target for the discovery of new anticancer drugs. We designed a novel structural class of KV1.3 inhibitors through structural optimization of benzamide-based hit compounds and structure-activity relationship studies. The potency and selectivity of the new KV1.3 inhibitors were investigated using whole-cell patch- and voltage-clamp experiments. 2D and 3D cell models were used to determine antiprolifera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The specific Kv1.3 channel inhibitor clofazimine, as a membrane-permeable small molecule organic compound, can inhibit cancer cell proliferation and induce cancer cell apoptosis through the mitochondrial pathway ( 9 ). The researchers found that the Kv1.3 inhibitor tetrahydropyran inhibited PC cell proliferation and induced apoptosis ( 58 ). In vitro experiments revealed that the mitochondrial Kv1.3 inhibitors PAPTP and PCARBTP were able to promote apoptosis in multiple myeloma cell lines L-363 and RPMI-8226 ( 67 ).…”
Section: Role Of Potassium Channel In Diagnosis and Treatment Of Tumormentioning
confidence: 99%
“…The specific Kv1.3 channel inhibitor clofazimine, as a membrane-permeable small molecule organic compound, can inhibit cancer cell proliferation and induce cancer cell apoptosis through the mitochondrial pathway ( 9 ). The researchers found that the Kv1.3 inhibitor tetrahydropyran inhibited PC cell proliferation and induced apoptosis ( 58 ). In vitro experiments revealed that the mitochondrial Kv1.3 inhibitors PAPTP and PCARBTP were able to promote apoptosis in multiple myeloma cell lines L-363 and RPMI-8226 ( 67 ).…”
Section: Role Of Potassium Channel In Diagnosis and Treatment Of Tumormentioning
confidence: 99%
“…Recently, Gubic and co-workers designed a novel structural class of small-molecule organic Kv1.3 channel inhibitors through structural optimisation of benzamide-based hit compounds and structure-activity relationship studies [30]. Structure optimisation resulted in a potent and selective Kv1.3 channel inhibitor (compound no 44) with an IC50 value of 470 nM for Kv1.3 channels expressed in Xenopus oocytes and 950 nM in Kv1.3 channel-expressing Ltk − cell line [30].…”
Section: Newly Designed Thiophene-based Inhibitorsmentioning
confidence: 99%
“…Recently, Gubic and co-workers designed a novel structural class of small-molecule organic Kv1.3 channel inhibitors through structural optimisation of benzamide-based hit compounds and structure-activity relationship studies [30]. Structure optimisation resulted in a potent and selective Kv1.3 channel inhibitor (compound no 44) with an IC50 value of 470 nM for Kv1.3 channels expressed in Xenopus oocytes and 950 nM in Kv1.3 channel-expressing Ltk − cell line [30]. Four most potent inhibitors (compounds no 14, 37, 43 and 44) significantly inhibited proliferation of Kv1.3 channel-expressing cell line Panc-1, whereas one inhibitor (hit compound no 4) induced apoptosis of Kv1.3 channel-expressing cell line Colo357 [30].…”
Section: Newly Designed Thiophene-based Inhibitorsmentioning
confidence: 99%
“…In the original publication [1], there was a mistake in Table 3 as published. The IC 50 value determined based on Ltk cells for PAP-1 is 1000 times lower.…”
mentioning
confidence: 99%
“…Table 3. Comparison of K V 1.3 IC 50 values for compounds 14, 37, 43, 44, and PAP-1 (1) obtained with HiClamp and manual voltage-clamp on Xenopus laevis oocytes (Tables 1 and 2) and with manual patch-clamp on the Ltk − cell-line.…”
mentioning
confidence: 99%